Predictive risk factor for difficult elective laparoscopic cholecystectomy in HUSM - Azmi, Mohd Azem Fathi Mohammad (2021)
Background : Laparoscopic cholecystectomy (LC) is a gold standard management for symptomatic cholelithiasis. However, LC might be difficult due to the various risk factors. Preoperative risk factors are very important for the surgeon and patient in anticipating of difficulty during surgery. The aim of this study to identify clinical, radiological, and perioperative risk factor with difficult elective laparoscopic cholecystectomy patient in HUSM. Methods: This is a retrospective record review of patients who underwent elective laparoscopic cholecystectomy from 2013 to 2018 in Hospital Universiti Sains Malaysia. The patient’s characteristics, clinical history, laboratory data, ultrasonography results and intraoperative details were retrospectively analyzed to evaluate predictors of difficult LC. Results: A total of 154 patients whom underwent elective laparoscopic cholecystectomy and fullfill the criteria were included in this study. The conversion rate to open surgey was 4.5%, the mean operative length was 91.71 minutes and the mean hospital stay post operative was one day. The prevalence of difficult elective laparoscopic cholecystectomy in HUSM was 55.2% (95% CI = 47.3, 63.0). Multivariate analysis showed that history of cholangitis , history of ERCP , thick gallbladder wall on ultrasound , dense adhesion and fibrosed Calot’s triangle intraoperatively had significant association with difficult laparoscopic cholecystectomy. Conclusion: From this study, it is concluded that patient’s history of cholangitis, history of ERCP, thick gallbladder wall on ultrasound, dense adhesion and fibrosed Calot’s triangle intraoperatively were found to be the predictive factors of difficult LC.